Comparing herbicide application methods with See & Spray™ technology in soybean - Avent, Tristen H.; Norsworthy, Jason K.; Patzoldt, William L.; Schwartz-Lazaro, Lauren M.; Houston, Michael M.; Butts, Thomas R.; Vazquez, Alan R. (Weed technology, 2024)
New machine-vision technologies like the John Deere See & Spray™ could provide the opportunity to reduce herbicide use by detecting weeds and target-spraying herbicides simultaneously. Experiments were conducted for 2 yr in Keiser, AR, and Greenville, MS, to compare residual herbicide timings and targeted spray applications versus traditional broadcast herbicide programs in glyphosate/glufosinate/dicamba-resistant soybean. Treatments utilized consistent herbicides and rates with a preemergence (PRE) application followed by an early postemergence (EPOST) dicamba application followed by a mid-postemergence (MPOST) glufosinate application. All treatments included a residual at PRE and excluded or included a residual EPOST and MPOST. Additionally, the herbicide application method was considered, with traditional broadcast applications, broadcasted residual + targeted applications of postemergence herbicides (dual tank), or targeted applications of all herbicides (single tank). Targeted applications provided comparable control to broadcast applications with a ≤1% decrease in efficacy and overall control ≥93% for Palmer amaranth, broadleaf signalgrass, morningglory species, and purslane species. Additionally, targeted sprays slightly reduced soybean injury by at most 5 percentage points across all evaluations, and these effects did not translate to a yield increase at harvest. The relationship between weed area and targeted sprayed area also indicates that nozzle angle can influence potential herbicide savings, with narrower nozzle angles spraying less area. On average, targeted sprays saved a range of 28.4% to 62.4% on postemergence herbicides. On the basis of these results, with specific machine settings, targeted application programs could reduce the amount of herbicide applied while providing weed control comparable to that of traditional broadcast applications. Nomenclature: Dicamba; glufosinate; glyphosate; broadleaf signalgrass, Urochloa platyphylla (Munro ex C. Wright) R.D. Webster; morningglory, Ipomoea spp.; Palmer amaranth, Amaranthus palmeri S. Watson; purslane, Portulaca spp.; soybean, Glycine max (L.) Merr.